Building the Integrity Fortress: A Holistic Performance Management and Accountability Model for Islamic Educational Institutions - Muhammad Halomoan; Husaini; Elidawati; Rahmat Hidayat (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Islamic educational institutions are currently facing an accountability crisis and the phenomenon of a